If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 8(x)(x) + 8x = 9(x)(x) Multiply x * x 2 + 8x2 + 8x = 9(x)(x) Reorder the terms: 2 + 8x + 8x2 = 9(x)(x) Multiply x * x 2 + 8x + 8x2 = 9x2 Solving 2 + 8x + 8x2 = 9x2 Solving for variable 'x'. Combine like terms: 8x2 + -9x2 = -1x2 2 + 8x + -1x2 = 9x2 + -9x2 Combine like terms: 9x2 + -9x2 = 0 2 + 8x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -2 + -8x + x2 = 0 Move the constant term to the right: Add '2' to each side of the equation. -2 + -8x + 2 + x2 = 0 + 2 Reorder the terms: -2 + 2 + -8x + x2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -8x + x2 = 0 + 2 -8x + x2 = 0 + 2 Combine like terms: 0 + 2 = 2 -8x + x2 = 2 The x term is -8x. Take half its coefficient (-4). Square it (16) and add it to both sides. Add '16' to each side of the equation. -8x + 16 + x2 = 2 + 16 Reorder the terms: 16 + -8x + x2 = 2 + 16 Combine like terms: 2 + 16 = 18 16 + -8x + x2 = 18 Factor a perfect square on the left side: (x + -4)(x + -4) = 18 Calculate the square root of the right side: 4.242640687 Break this problem into two subproblems by setting (x + -4) equal to 4.242640687 and -4.242640687.Subproblem 1
x + -4 = 4.242640687 Simplifying x + -4 = 4.242640687 Reorder the terms: -4 + x = 4.242640687 Solving -4 + x = 4.242640687 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 4.242640687 + 4 Combine like terms: -4 + 4 = 0 0 + x = 4.242640687 + 4 x = 4.242640687 + 4 Combine like terms: 4.242640687 + 4 = 8.242640687 x = 8.242640687 Simplifying x = 8.242640687Subproblem 2
x + -4 = -4.242640687 Simplifying x + -4 = -4.242640687 Reorder the terms: -4 + x = -4.242640687 Solving -4 + x = -4.242640687 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = -4.242640687 + 4 Combine like terms: -4 + 4 = 0 0 + x = -4.242640687 + 4 x = -4.242640687 + 4 Combine like terms: -4.242640687 + 4 = -0.242640687 x = -0.242640687 Simplifying x = -0.242640687Solution
The solution to the problem is based on the solutions from the subproblems. x = {8.242640687, -0.242640687}
| 3x+32=5x+24 | | 13-3p=-15-6p | | n^2-8n-6=n | | 9-5k=1-7k | | n^2+14n-5=10 | | 5x-39=42+2x | | Y^2+y-812=0 | | 2(d+7)-7=9 | | K^2-11k=14 | | x+50+2x-20=180 | | 2.5*-10= | | (6x+7)=(r-2) | | 4x+2(-7+2g)=1-g | | 12x+4=138 | | 3(x-10)+2(x-29)=2 | | 4x+2(-7+2g)=1g | | x+19+4x=-16-4x-19 | | 2b-4-7b-3= | | 3-4a=11-3a | | 4(n-7)=3n | | -(-7-6m)-5=-2(-6m+8) | | -3x-6(-5x+5)=159 | | 2(3x+9)=-50+14 | | 20x+5=x+89 | | 0.51x-22+1.76=0.3x+0.8 | | 5(y-4)-4=-4(-4y+9)-3y | | 4(m+2)-4m-8= | | 112=-8(x-6) | | 7.3=-2.2c-2.9+c | | 2250000x(80-p)=2000000x(p-20) | | -2n+3=-5(6n-5)+6n | | 12x-3(x-5)=-48 |